Koneksi Matematis dan Berpikir Kreatif dalam Pembelajaran Matematika dengan Teori APOS - Retno Marsitin (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
This study aimed to describe the mathematical connection capability and creative thinking in mathematics with APOS theory. This study uses a quantitative and qualitative approach, the research design class action, which was conducted in two cycles. The research subject is 30 math education students who take a course in calculus. The results showed that an increase in the ability to connect mathematical and creative thinking in mathematics with APOS theory which includes Action, Process, Object and Scheme. This is shown by the data obtained in the second cycle that meets the criteria of academic success with 81.47%, the ability of mathematical connection with the achievement of 80.56%, and the ability to think creatively with the achievement of 81.27%.